2022
DOI: 10.1039/d2qi00959e
|View full text |Cite
|
Sign up to set email alerts
|

Constructing NiCo2Se4/NiCoS4 heterostructures for high-performance rechargeable aluminum battery cathodes

Abstract: An aluminum battery based on the NiCo2Se4/NiCoS4 cathode delivers a capacity of 112 mA h g−1 after 195 cycles. The charge–discharge principle of the NiCo2Se4/NiCoS4 cathode is the Al3+ intercalation and valence state transition of the Ni, Co, and S elements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…For the charge/discharge curves (Figure d), the discharge potential plateau around 0.3 V and charge potential plateau around 1.1 V are well consistent with the previous CV profiles. Figure e indicates that the heterostructured FeSe 2 /MoS 2 is provided with superior electrochemical performance among the outstanding cathode materials that have been reported. , In general, the heterostructured FeSe 2 /MoS 2 exhibits splendid reversible capacity, cycling stability, and rate performance, which are attributed to the good reaction kinetics and structural stability resulting from interfacial engineering.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…For the charge/discharge curves (Figure d), the discharge potential plateau around 0.3 V and charge potential plateau around 1.1 V are well consistent with the previous CV profiles. Figure e indicates that the heterostructured FeSe 2 /MoS 2 is provided with superior electrochemical performance among the outstanding cathode materials that have been reported. , In general, the heterostructured FeSe 2 /MoS 2 exhibits splendid reversible capacity, cycling stability, and rate performance, which are attributed to the good reaction kinetics and structural stability resulting from interfacial engineering.…”
Section: Resultsmentioning
confidence: 90%
“…It is worth pointing out that interfacial engineering is considered as a fantastic method to heighten electrochemical storage performance. The built-in electric field formed at the interfaces of the heterogeneous mixture is anticipated to lower the diffusion barrier and speed up the mobility of charge carriers by enhancing the kinetics of the interfacial reaction, thereby expected to significantly enhance the extraction/intercalation of AlCl 4 – during cycling. , Furthermore, the abundance of defects and lattice distortion at interfaces will provide facile ion diffusion pathways and additional reaction active sites for electrochemical storage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensity of Al 2p in the fully discharged state was distinctly stronger than that in the fully charged state, conrming that the embedding of Al 3+ cations occurs during the discharging process. 45,46 In the Cl 2p spectra, the peaks at 202.5 eV and 200.7 eV showed limited variation at 0.01 V and 1.8 V. Interestingly, the characteristic peak of the Al-Cl bond located at 198.9 eV became signicantly stronger at 1.8 V, which reects that the AlCl 4 − anions may also act as carriers and are embedded in cathode during the charging process. 47,48 Therefore, it can be concluded that the S-MoS 2 cathode operates through the coordination of Al 3+ and AlCl 4 − .…”
Section: Electrochemical Performancementioning
confidence: 98%